Nanoscale distribution of TLR4 on primary human macrophages stimulated with LPS and ATI. Issue 19 (8th May 2019) - Neumann, Jan; Ziegler, Kira; Gelléri, Márton; Fröhlich-Nowoisky, Janine; Liu, Fobang; Bellinghausen, Iris; Schuppan, Detlef; Birk, Udo; Pöschl, Ulrich; Cremer, Christoph; Lucas, Kurt
Abstract : Localization microscopy reveals donor-dependent membrane distribution of Toll-like receptor 4 (TLR4) on primary human macrophages. Abstract : Toll-like receptor 4 (TLR4) plays a crucial role in the recognition of invading pathogens. Upon activation by lipopolysaccharides (LPS), TLR4 is recruited into specific membrane domains and dimerizes. In addition to LPS, TLR4 can be stimulated by wheat amylase-trypsin inhibitors (ATI). ATI are proteins associated with gluten containing grains, whose ingestion promotes intestinal and extraintestinal inflammation. However, the effect of ATI vs. LPS on the membrane distribution of TLR4 at the nanoscale has not been analyzed. In this study, we investigated the effect of LPS and ATI stimulation on the membrane distribution of TLR4 in primary human macrophages using single molecule localization microscopy (SMLM). We found that in unstimulated macrophages the majority of TLR4 molecules are located in clusters, but with donor-dependent variations from ∼51% to ∼75%. Depending on pre-clustering, we found pronounced variations in the fraction of clustered molecules and density of clusters on the membrane upon LPS and ATI stimulation. Although clustering differed greatly among the human donors, we found an almost constant cluster diameter of ∼44 nm for all donors, independent of treatment. Together, our results show donor-dependent but comparable effects between ATI and LPS stimulation on the membrane distribution of TLR4. This may indicate a general mechanism of TLR4 activation in primary human macrophages. Furthermore, our methodology visualizes TLR4 receptor clustering and underlines its functional role as a signaling platform.